THE INFLUENCE OF THE PROBLEM BASED LEARNING (PBL) ASSISTED WITH WORDWALL EDUCATIONAL GAMES ON CRITICAL THINKING ABILITY - Aprilia Putri Rahayu; Triman Juniarso; Amelia Widya Hanindita (Jurnal IPA Terpadu, 2024)
This research was motivated by students' difficulties in participating in active learning and finding concepts independently, caused by the dominance of learning material that came from teachers, who rarely involved students in the concept discovery process. The research aimed to determine the influence of the Problem Based Learning (PBL) learning model assisted by the wordwall educational game on critical thinking skills in the science subject of fourth-grade elementary school students. The study employed the True Experimental approach with a Pretest-Posttest Control Group Design. The study's population consisted of fourthgrade students at SDN Sumur Welut III/440 Surabaya, divided into two sample groups: the experimental and control classes, each consisting of 22 students. Random sampling was used as the sampling technique. Data collection methods included tests and interviews. The data analysis involved prerequisite tests such as normality and homogeneity tests, while hypothesis testing utilized the independent sample t-test. The findings indicated that the experimental class's critical thinking ability yielded an average posttest score of 1682, whereas the control class obtained an average posttest score of 1430. The hypothesis results showed a Sig (2-tailed) value of 0.000 < 0.05 which meant  was rejected and  was accepted. Therefore, the conclusion of this research was that there was an influence of the Problem Based Learning (PBL) learning model assisted by the wordwall educational game on critical thinking skills in the science subject of fourthgrade elementary school students.